Investigating the use of Marigolds (Tagetes spp.) and brassicaceous cover crops as a tool for the management of lesion nematodes (Pratylenchus spp.) in apple orchards - Fourie, Louis Welricht (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScConsEcol)--Stellenbosch University, 2024.